2020
DOI: 10.1007/s11356-020-08217-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key sectors based on cascading effect along paths in the embodied CO2 emission flow network in Beijing-Tianjin-Hebei region, China

Abstract: For the past few years, the Consumer Internet of Things (CIoT) has entered public lives. While CIoT has improved the convenience of people's daily lives, it has also brought new security and privacy concerns. In this survey, we try to figure out what researchers can learn about the security and privacy of CIoT by traffic analysis, a popular method in the security community. From the security and privacy perspective, this survey seeks out the new characteristics in CIoT traffic analysis, the state-of-the-art pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 188 publications
(305 reference statements)
0
1
0
Order By: Relevance
“…This chain of reduced financial flows can spread through the system, potentially leading to positive feedback dynamics and resulting in a strong reduction of the total net worth of financial institutions (Calvo et al, 2004). Relevant research has confirmed the cascade conduction effect of networks and the impact of network structure on network function (Jia et al, 2020;Jia et al, 2019;Li et al, 2022;Li et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…This chain of reduced financial flows can spread through the system, potentially leading to positive feedback dynamics and resulting in a strong reduction of the total net worth of financial institutions (Calvo et al, 2004). Relevant research has confirmed the cascade conduction effect of networks and the impact of network structure on network function (Jia et al, 2020;Jia et al, 2019;Li et al, 2022;Li et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…With the sense of responsibility, China has not stopped ecological civilization (Gu et al,2020). China is striving to peak carbon dioxide emissions by 2030 and achieve carbon neutral by 2060 Jia et al,2020). The main objectives of Chinese government are: by 2025, the economic system of green, low-carbon and cyclic development will have taken initial shape, and the efficiency of energy use in key sectors will have increased significantly.…”
Section: Introductionmentioning
confidence: 99%